PENGARUH KONSENTRASI PUPUK ORGANIK CAIR DAN TAKARAN PUPUK NITROGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) KULTIVAR DEWATA F1 - Gustaf Rifaldy (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2019)
This study aimed to determine: (1) the combination of the effect of liquid organic fertilizer (LOF) concentration and nitrogen fertilizer dose on the growth and yield of cayenne pepper (Capsicum frutescens L.) cultivar Dewata F1 (2) the effect of LOF concentration and nitrogen fertilizer dose which gave the best influence on growth and the results of cayenne pepper (Capsicum frutescens L.) cultivar Dewata F1 (3) correlation between growth components and yield of cayenne pepper (Capsicum frutescens L.) cultivar Dewata F1. The study was conducted in Nanggerang Village, Jalaksana District, Kuningan-West Java Regency, from July to October 2018. The method used in this research was the experimental method. The experimental design used was Randomized Block Design (RBD). This experiment consisted of 12 combinations of liquid organic fertilizer concentration and nitrogen fertilizer dosage, each of which was repeated three times, so that there were 36 experimental plots. The combination of treatments tested in the field are: A = LOF 0%, N = 67.5 kg / ha (150 kg Urea), B = LOF 0%, N = 90.0 kg / ha (200 kg Urea), C = LOF 0%, N = 112.5 kg / ha (250 kg Urea), D = LOF 15%, N = 67.5 kg / ha (150 kg Urea), E = LOF 15%, N = 90.0 kg / ha (200 kg Urea), F = LOF 15%, N = 112.5 kg / ha (250 kg Urea), G = LOF 20%, N = 67.5 kg / ha (150 kg Urea), H = LOF 20%, N = 90.0 kg / ha (200 kg Urea), I = LOF 20%, N = 112.5 kg / ha (250 kg Urea), J = LOF 25%, N = 67.5 kg / ha (150 kg Urea), K = LOF 25%, N = 90.0 kg / ha (200 kg Urea), L = LOF 25%, N = 112.5 kg / ha (250 kg Urea). The results showed that combination of liquid organic fertilizer concentration and dose of nitrogen fertilizer did not affect to all observed variables except for stem diameter at 21 DAP. There was correlation between the components of growth and the fruit weight of the crop.